1997
DOI: 10.1021/la961085d
|View full text |Cite
|
Sign up to set email alerts
|

Sequential Saturating Reactions of ZrCl4 and H2O Vapors in the Modification of Silica and γ-Alumina with ZrO2

Abstract: Zirconia-modified silica and alumina samples were prepared by the atomic layer epitaxy technique using successive saturating reactions of ZrCl4 and H2O vapors. The growth of ZrO2 was followed by X-ray diffraction, diffuse reflectance IR Fourier transform spectroscopy, and 1H magic angle spinning NMR measurements. In addition, coverage of the silica surface was estimated by low-energy ion scattering (LEIS). At the reaction temperature of 300 °C the main reaction of ZrCl4, on both supports, occurred with surface… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(21 citation statements)
references
References 47 publications
0
21
0
Order By: Relevance
“…The actual deposition process is discussed in detail in earlier publications. [21][22][23][24][25][28][29][30] Pyridine adsorption was performed after calcination of the samples at 500°C for 16h, and subsequent degassing at 150°C for 3 h. The samples were exposed to pyridine vapor for 30 min. After evacuation for 3 h at 150°C, the FTIR-PAS spectra were recorded.…”
Section: Methodsmentioning
confidence: 99%
“…The actual deposition process is discussed in detail in earlier publications. [21][22][23][24][25][28][29][30] Pyridine adsorption was performed after calcination of the samples at 500°C for 16h, and subsequent degassing at 150°C for 3 h. The samples were exposed to pyridine vapor for 30 min. After evacuation for 3 h at 150°C, the FTIR-PAS spectra were recorded.…”
Section: Methodsmentioning
confidence: 99%
“…[9,10] Ti(OH) m Cl 4±m is likely to represent relatively stable intermediates, as large TiO 2 crystals form in the saturating reaction of TiCl 4 with porous silica. [8] As examples of stable oxychlorides, TaOCl 3 and NbOCl 3 can be mentioned; these are transported, unreacted, out of the reactor during ALD processing.…”
Section: Effect Of MCL N Reactant On Mo N/2 Particle Formationmentioning
confidence: 99%
“…Compared to the TiO 2 particles observed on high surface area substrates, the ZrO 2 particles were considerably smaller, with dimensions in the order of 10 nm. [10] Kytökivi et al [9] suggested that the ZrO 2 particles could originate from the formation and decomposition of hydroxychloride Zr(OH) m Cl 4±m or oxychloride ZrOCl 2 intermediates. Kytö-kivi and Haukka [11] showed, by infrared measurements, that the TiO 2 and ZrO 2 particles are bonded to the silica substrate through Si±O±Ti and Si±O±Zr bonds, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…With no evidence of the monoclinic phase, nanocrystalline tetragonal ZrO 2 could be obtained in non-doped ultrathin ZrO 2 layers, 5±15 nm thick or below. [17,18] Films of monoclinic ZrO 2 had permittivity values of 20, while the nanolaminates, consisting of amorphous Ta 2 O 5 and tetragonal ZrO 2 , had a permittivity value as high as 33. [17] To date, no reports have been published on the application of alkoxide or metal±organic Zr precursors in the ALD process.…”
Section: Zr±o±zr[oc(ch 3 ) 3 ] 3 * ± ?mentioning
confidence: 99%